Accountability and Transparency of the Electronic Court and Litigation Systems in Indonesia - Mukhtar, Mukhtar; Lailam, Tanto (Jurnal Hukum, 2023)
The research focuses on evaluating and strengthening the electronic justice system in Indonesia, with a particular emphasis on its accountability and transparency. It is motivated by the numerous challenges in the electronic justice system implementation related to regulations, human resources, case management, and other potential emerging problems. This research employed normative and empirical legal methods. The research results reveal that electronic justice systems may be classified within the appropriate category. The most important thing is to strengthen the accountability and transparency in it towards an independence and impartiality of the electronic judiciary system through strengthening the quality assurance of the electronic judiciary system, electronic administration of the judiciary system by a clerk court based on an electronic trial recording (e-records), data security guarantees in e-court and e-litigation processes, and unlimited access assurance to space and time.